Theological Review of the Concept of Feng Shui According to Colossians 2:8 - Yulianto, Auw Tammy; Simon, Simon; Cahyadi, Tjiong Eric (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
Feng shui was a part of the cultural heritage of ancient Chinese society mainly used to design buildings and spaces according to the birth date or the basic elements of the owner or the person who occupied a building to achieve harmony and balance with the environment aimed to bring peace and prosperity. Feng shui practices had become a matter of debate among Christians. The question was whether feng shui practices such as calculations in building construction, determining the direction a tomb should face, or finding a date to start a business did not conflict with God's Word. From a non-theological point of view,Â feng shui was well accepted because it seemed reasonable. This article discussed feng shui from a theological perspective by referring to Colossians 2:8. In the research of this article, the researchers used a qualitative descriptive method with an exposition approach where data collection was obtained from literature studies and interviews. The results of the discussion on this topic showed that theologians concurred that feng shui did not correspond with God's Word, while the Bible interpreted feng shui as a false philosophy. The conclusion drawn was the rejection of feng shui practices by theologians and the Bible.